6&6: A Transdisciplinary Approach to Art–Science Collaboration. (29th July 2020) - Clark, Sarah E; Magrane, Eric; Baumgartner, Thomas; Bennett, Scott E K; Bogan, Michael; Edwards, Taylor; Dimmitt, Mark A; Green, Heather; Hedgcock, Charles; Johnson, Benjamin M; Johnson, Maria R; Velo, Kathleen; et al.
Abstract: Despite an historical connection between the arts and sciences, in the past century, the two disciplines have been greatly siloed. However, there is a renewed interest in collaboration across the arts and sciences to support conservation practice by understanding and communicating complex environmental, social, and cultural challenges in novel ways. 6&6 was created as a transdisciplinary art–science initiative to promote a deeper appreciation of the Sonoran Desert. Six artists and six scientists were paired to create work that explored conservation issues in the Sonoran Desert and the Gulf of California. In-depth interviews were conducted with the artists and scientists throughout the 4-year initiative to understand the impact of 6&6 on their personal and professional behaviors and outlook. The findings from this case study reveal the role that intensive, place-based, and transdisciplinary art–science programs can play in shaping narratives to better communicate the patterns and processes of nature and human–environment interactions.